1987
DOI: 10.1152/ajpheart.1987.253.2.h412
|View full text |Cite
|
Sign up to set email alerts
|

Temporal relation between energy metabolism and myocardial function during ischemia and reperfusion

Abstract: The purpose of the present investigation was to study the relation between energy metabolism and contractile function in the isovolumic guinea pig heart. 31P nuclear magnetic resonance spectroscopy was used to measure changes in the intracellular levels of creatine phosphate, ATP, inorganic phosphate, and pH during 2.43 min total global ischemia and 2.43 min reperfusion, with a time resolution of 9.7 s. From these data, cytosolic changes in the phosphorylation potential, [ATP]-to-[ADP] ratio, free-energy chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 0 publications
3
42
0
Order By: Relevance
“…Although the relationship between myocardial high-energy phosphates and function has been investigated in perfused hearts (18)(19)(20)(21) and after total coronary occlusion in vivo (1,2), there are only limited data concerning this relationship during partial reductions in regional myocardial blood flow (22,23). We have previously demonstrated that changes in high-energy phosphates, especially the PCr/Pi ratio, correlate closely with changes in myocardial blood flow under conditions of steadystate regional ischemia (24).…”
Section: Introductionmentioning
confidence: 99%
“…Although the relationship between myocardial high-energy phosphates and function has been investigated in perfused hearts (18)(19)(20)(21) and after total coronary occlusion in vivo (1,2), there are only limited data concerning this relationship during partial reductions in regional myocardial blood flow (22,23). We have previously demonstrated that changes in high-energy phosphates, especially the PCr/Pi ratio, correlate closely with changes in myocardial blood flow under conditions of steadystate regional ischemia (24).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] However, the most rapid and pronounced changes in myocardial contractile function and energy metabolism occur during the first 30 seconds of ischemia and during the initial period of recovery after a brief ischemic interval. [8][9][10][11][12][13] Elucidating the dynamic relation between such large and rapid changes in cardiac contractile function and energy metabolism may help define the mechanisms by which cardiac contractility is regulated during and following ischemia.…”
mentioning
confidence: 99%
“…Some studies suggest that vascular collapse may be an important mediator of contractile depression after acute no-flow ischemia (29,30). However, other studies have demonstrated a close relationship between the initial fall of pressure and energy phosphate metabolites after acute noflow ischemia, suggesting that vascular collapse is not important in mediating contractile depression (31,32).…”
Section: Discussionmentioning
confidence: 99%